A Rare Case of Incidental Pancreatic Arteriovenous Malformation Correctly Diagnosed with MDCT - De Robertis Lombardi, Riccardo; D'Onofrio, Mirko; Crosara, Stefano; Canestrini, Stefano; Demozzi, Emanuele; Pozzi Mucelli, Roberto (JOP. Journal of the Pancreas, 2013)
Context Pancreatic arteriovenous malformations are a rare entity that can be incidentally discovered during MDCT examinations. Case report We describe a rare case of asymptomatic arteriovenous malformation presenting at MDCT as a hypervascular mass in the pancreatic head. Conclusion Pancreatic arteriovenous malformations are a rare entity, often asymptomatic, that can be correctly diagnosed by MDCT, especially with the use of specific electronic reconstructions. Image: 3D paracoronal MIP arterial phase reconstruction.